(3p-7)(2p+8)=

Simple and best practice solution for (3p-7)(2p+8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3p-7)(2p+8)= equation:


Simplifying
(3p + -7)(2p + 8) = 0

Reorder the terms:
(-7 + 3p)(2p + 8) = 0

Reorder the terms:
(-7 + 3p)(8 + 2p) = 0

Multiply (-7 + 3p) * (8 + 2p)
(-7(8 + 2p) + 3p * (8 + 2p)) = 0
((8 * -7 + 2p * -7) + 3p * (8 + 2p)) = 0
((-56 + -14p) + 3p * (8 + 2p)) = 0
(-56 + -14p + (8 * 3p + 2p * 3p)) = 0
(-56 + -14p + (24p + 6p2)) = 0

Combine like terms: -14p + 24p = 10p
(-56 + 10p + 6p2) = 0

Solving
-56 + 10p + 6p2 = 0

Solving for variable 'p'.

Factor out the Greatest Common Factor (GCF), '2'.
2(-28 + 5p + 3p2) = 0

Factor a trinomial.
2((-4 + -1p)(7 + -3p)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-4 + -1p)' equal to zero and attempt to solve: Simplifying -4 + -1p = 0 Solving -4 + -1p = 0 Move all terms containing p to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1p = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1p = 0 + 4 -1p = 0 + 4 Combine like terms: 0 + 4 = 4 -1p = 4 Divide each side by '-1'. p = -4 Simplifying p = -4

Subproblem 2

Set the factor '(7 + -3p)' equal to zero and attempt to solve: Simplifying 7 + -3p = 0 Solving 7 + -3p = 0 Move all terms containing p to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -3p = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -3p = 0 + -7 -3p = 0 + -7 Combine like terms: 0 + -7 = -7 -3p = -7 Divide each side by '-3'. p = 2.333333333 Simplifying p = 2.333333333

Solution

p = {-4, 2.333333333}

See similar equations:

| 10x+6=-7 | | 2[3x+4]=19 | | 4n+1=36 | | 0.26x+0.07(60000-x)=11040 | | 0=5x^(2/3)-2x^(5/3) | | -2-5x+2= | | 1/2[5-x]=1/4 | | -2xy^2(3x-2y)= | | 7z-6=5 | | x^3-8x+8=0 | | 10x-5=x+8 | | 9^-5x^4/9^-3x^-1= | | 7(u-6)=-7 | | 5x-3x-24=8x-2x+24 | | 43/29=24/x | | =32-[9-3(4-10)]+(2-5)3 | | 12+6x=8-4x | | 8[x+6]-3x=18 | | 18(v+1)-2v=4(4v+4)-21 | | 6(7x-8)=246 | | (-4x^2y)(3x^4)(-2xy^5)= | | 3+8z-12=2z-9+z | | 8(5x-11)=112 | | 5x^2+9x-165=0 | | 10(7x+14)=490 | | 6(7x+6)=246 | | -9(v+3)+2v+7=5v+11 | | Sin^2(x)+9sin(x)+8=0 | | (2x+3)(3x^2-2x+1)= | | 6n=0.84 | | 15x-13=12x+41 | | 105-3t-32+8t-20=-72+6t-4 |

Equations solver categories